2023
DOI: 10.31891/2307-5732-2023-319-1-15-19
|View full text |Cite
|
Sign up to set email alerts
|

STUDY OF THE EFFECT OF PRECURSORS ON THE STRUCTURAL CHARACTERISTICS OF SYNTHETIZED ZnO NANOPARTICLES

Abstract: In this work, zinc oxide (ZnO) nanoparticles were obtained by direct precipitation method in aqueous solution using two different precursors — zinc acetate dihydrate and zinc chloride — under the same synthesis conditions. The effect of the selected precursors on the structural parameters of each synthesized sample was evaluated using X-ray diffraction (XRD) analysis. The results of the analysis demonstrate the synthesized ZnO phase with a hexagonal wurtzite structure and the average crystallite size of 28 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 10 publications
3
3
0
Order By: Relevance
“…For comparison, in [16] the characteristics of the crystalline structure of ZnO nanoparticles synthesized from Zn(NO 3 ) 2 •4H 2 O by a similar method of direct deposition at different temperatures (60 °С, 80 °С, 100 °С) for 2 h are given, and it is shown that that the smallest crystallite size of 44 nm is formed at 80 °C with calcination at 500 °C for 5 h. The advantages of the synthesis method proposed in this paper are the possibility to obtain nanoparticles of smaller size at lower temperatures in a shorter time. This can be explained by the effect of the selected precursor Zn(CH 3 COO) 2 •2H 2 O on the parameters of the formed crystal structure, which confirms the results of study [14].…”
Section: Discussion Of Results Of Investigating the Effectiveness Of ...supporting
confidence: 86%
See 4 more Smart Citations
“…For comparison, in [16] the characteristics of the crystalline structure of ZnO nanoparticles synthesized from Zn(NO 3 ) 2 •4H 2 O by a similar method of direct deposition at different temperatures (60 °С, 80 °С, 100 °С) for 2 h are given, and it is shown that that the smallest crystallite size of 44 nm is formed at 80 °C with calcination at 500 °C for 5 h. The advantages of the synthesis method proposed in this paper are the possibility to obtain nanoparticles of smaller size at lower temperatures in a shorter time. This can be explained by the effect of the selected precursor Zn(CH 3 COO) 2 •2H 2 O on the parameters of the formed crystal structure, which confirms the results of study [14].…”
Section: Discussion Of Results Of Investigating the Effectiveness Of ...supporting
confidence: 86%
“…The results of X-ray diffraction analysis (Fig. 1) show that ZnO nanoparticles are formed in a hexagonal wurtzite structure with an average crystallite size of 28 nm [14]. The calculated structural parameters of the synthesized ZnO nanoparticles are in good agreement with the standard data (JCPDS 36-1451).…”
Section: Synthesis and Morphological Analysissupporting
confidence: 68%
See 3 more Smart Citations